Kedudukan Peraturan Presiden Dalam Hierarki Peraturan Perundang-Undangan Indonesia - Putri Karimah Harahap (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
Presidential Regulation is one form of legislation that has legal force in Indonesia. However, there is still ambiguity regarding the position of the Presidential Regulation in the hierarchy of legislation as stated in Article 7 paragraph (1) of Law No. 12 of 2011 in conjunction with Law No. 13 of 2022 concerning the Formation of Legislation. This study aims to legally analyze the position of the Presidential Regulation in the hierarchical structure of Indonesian legislation. The method used in this study is the normative legal method. The results of the study indicate that the Presidential Regulation is below the Law and Government Regulation, but has a strategic function in implementing higher regulatory provisions. The conclusion of this study emphasizes the importance of rearranging the hierarchy of regulations to avoid normative conflicts and ensure legal certainty.